THE EFFECTIVENESS OF MULTIMODAL LEARNING (TEXT + VIDEO + AI) IN VOCABULARY ACQUISITION AMONG UZBEK EFL STUDENTS - Zokirova Marjona Xislatjon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
This study investigates the effectiveness of multimodal learning— combining text, video, and artificial intelligence (AI) tool —in enhancing vocabulary acquisition among Uzbek EFL (English as a Foreign Language) students. The research explores how integrating multiple modes of input improves learners’ engagement, retention, and understanding of new vocabulary. It also examines the role of AI in providing personalized feedback and adaptive learning experiences. Findings highlight the potential benefits and challenges of multimodal approaches in EFL contexts.